2023
DOI: 10.3390/cells12182300
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Progenitor Cell Exosomal miR-935 Protects against Oxidative Stress

Susana Aguilar,
Paula García-Olloqui,
Lidia Amigo-Morán
et al.

Abstract: Oxidative stress-induced myocardial apoptosis and necrosis are critically involved in ischemic infarction, and several sources of extracellular vesicles appear to be enriched in therapeutic activities. The central objective was to identify and validate the differential exosome miRNA repertoire in human cardiac progenitor cells (CPC). CPC exosomes were first analyzed by LC-MS/MS and compared by RNAseq with exomes of human mesenchymal stromal cells and human fibroblasts to define their differential exosome miRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…As mentioned previously, exosomes from CPCs have a regenerative potential, which aids in cardiac regeneration after myocardial infarction. Several studies have shown that they can suppress cell apoptosis in CMs and the development of fibrosis while potentiating tube formation, resulting in improved cardiac function [ 107 ]. The expression levels of the CM and EC genes in CPC increase when stimulated by embryonic stem cell (ES)-derived exosomes.…”
Section: Exosomes As Therapeutic Agents For Cardiovascular Diseasesmentioning
confidence: 99%
“…As mentioned previously, exosomes from CPCs have a regenerative potential, which aids in cardiac regeneration after myocardial infarction. Several studies have shown that they can suppress cell apoptosis in CMs and the development of fibrosis while potentiating tube formation, resulting in improved cardiac function [ 107 ]. The expression levels of the CM and EC genes in CPC increase when stimulated by embryonic stem cell (ES)-derived exosomes.…”
Section: Exosomes As Therapeutic Agents For Cardiovascular Diseasesmentioning
confidence: 99%